Evaluation of single-delay arterial spin labeling-based spatial coefficient of variation and histogram-based parameters in relation to cerebrovascular reserve in patients with Moyamoya disease - Fahlström, Markus; Svedung Wettervik, Teodor; Enblad, Per; Lewén, Anders; Wikström, Johan (Frontiers in Neurology, 2023)
Introduction Single-delay Arterial Spin Labeling (ASL)-based spatial coefficient of variation (CoVCBF) has been suggested as a measure of hemodynamic disturbance in patients with cerebrovascular diseases. However, spatial CoVCBF and other histogram-based parameters such as skewness and kurtosis and the volume of the arterial transit time artefact (ATAvol), has not been evaluated in patients with MMD nor against cerebrovascular reserve (CVR). The aim of this study was to assess whether any associations between spatial CoVCBF, skewness, kurtosis, and ATAvol are present and to analyze any potential associations with CVR, derived from single-delay ASL in patients with MMD. Methods Fifteen MMD patients were included before or after revascularization surgery. Cerebral blood flow (CBF) maps were acquired using pseudo-continuous ASL before, and 5, 15, and 25 min after an intravenous acetazolamide injection. CVRmax was defined as the highest percentual increase in CBF at any of the three post-injection time points. A vascular territory template was spatially normalized to each patient, including the bilateral anterior, middle, and posterior cerebral arteries. All affected anterior and middle cerebral artery regions and all unaffected posterior cerebral artery regions were included, based on Suzuki grading by digital subtraction angiography. Results Significant differences between affected and unaffected regions were found for CBF, CVRmax, and ATAvol. No association was found between CVRmax and any other parameter. High correlations were found between spatial CoVCBF, skewness and ATAvol. Conclusion Spatial CoVCBF derived from single-delay ASL does not correlate with CVR in patients with MMD. Moreover, skewness and kurtosis did not provide additional information of clinical value.